The Relationship Between Social Anxiety And Internet Addiction Among Unimas Undergraduate Nursing Students - Nuhilhadiah, Suatman (Universiti Malaysia Sarawak (UNIMAS), 2023)
Introduction: With a steadily rising prevalence globally, social anxiety and internet addiction have emerged as major public health issues including among nursing students. Objective: The present study was conducted to assess the prevalence of social anxiety, the prevalence of internet addiction and to determine the relationship between social anxiety and internet addiction among UNIMAS undergraduate nursing students. Method: In this study, a quantitative research, cross-sectional study and simple random sampling method were implemented among 146 UNIMAS undergraduate nursing students to screen for social anxiety using Social Phobia Inventory (SPIN) and to screen for internet addiction using Internet Addiction Test (IAT). The data was analyzed using Spearmen Correlation of IBM SPSS version 26. Result: The majority of respondents were between the ages of 19 and 29 years old (M= 21.69, SD= 1.357). The mean prevalence of social anxiety was 34.41 and the standard deviation was 13.864 (M= 34.41, SD= 13.864) while the mean prevalence of internet addiction is 36.76, and the standard deviation is 16.783 (M = 36.76, SD = 16.783). The study found that the relationship between social anxiety and internet addiction were weak correlated yet positively correlated (rs = 0.456, p = 0.0001). Conclusion: The UNIMAS undergraduate nursing students have a significant prevalence of social anxiety and almost half of the students had an addiction to the internet and there was a weak positive correlation between social anxiety and internet addiction. These findings offer baseline information for preventive measures of getting social anxiety and internet addiction that can be used for nursing department.